2017
DOI: 10.1016/j.jsbmb.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with aromatase inhibitors stimulates the expression of epidermal growth factor receptor-1 and neuregulin 1 in ER positive/HER-2/neu non-amplified primary breast cancers

Abstract: While estrogens have been shown to modulate EGFR/HER-1 and HER-2/neu expression in experimental systems, the effects of estrogen deprivation on expression levels of the HER-receptors and the neuregulin (NRG)1 ligand in breast cancers remain unknown. Here, we measured EGFR/HER-1-4 and NRG1 mRNA in ER positive tumors from 85 postmenopausal breast cancer patients before and after two weeks (n=64) and three months (n=85) of primary treatment with an aromatase inhibitor (AI). In tumors lacking HER-2/neu amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
(103 reference statements)
1
2
0
Order By: Relevance
“…They are located in the mucosal layer, both in cells located in the submucosal layer identified as macrophages, as well as in the neuronal cells of the ENS [78,79] and they are involved in many processes including, among others, intestinal motility, inflammatory reactions, cell proliferation, regulation of mitochondrial function and protective processes (for review, see [80]). Since BPA is known as a ligand of the estrogen receptors, and previous studies also linked the levels of NRG 1 expression with endocrine resistance [81,82], the changes noted in the present study may result from endocrine disruption caused by BPA.…”
Section: Discussionsupporting
confidence: 52%
“…They are located in the mucosal layer, both in cells located in the submucosal layer identified as macrophages, as well as in the neuronal cells of the ENS [78,79] and they are involved in many processes including, among others, intestinal motility, inflammatory reactions, cell proliferation, regulation of mitochondrial function and protective processes (for review, see [80]). Since BPA is known as a ligand of the estrogen receptors, and previous studies also linked the levels of NRG 1 expression with endocrine resistance [81,82], the changes noted in the present study may result from endocrine disruption caused by BPA.…”
Section: Discussionsupporting
confidence: 52%
“…In EGFR- and HER2-overexpression transgenic models larger tumors appear that respond to tyrosine kinase inhibitors [ 68 ]. Although the relation among aromatase, estrogens, and EGFR have been studied in different tumors such as breast [ 69 ], endometrial [ 70 ], lung [ 71 ], and liver [ 72 ] tumors, among others, the relationship between EGFR and aromatase in pituitary gland or prolactinomas has not been well analyzed to date, but its participation should not be ruled out.…”
Section: Estrogens Prolactin and Aromatasementioning
confidence: 99%
“…While downstream signaling by NRG-1 proteins is well studied, transcriptional regulation of the NRG-1 gene is poorly understood. Chronic stress, exercise training, estrogen deprivation, vitamin D and antipsychotic drugs increase NRG-1 expression [16,17,18,19]. The only study that has characterized the NRG-1 promoter showed that it contained Sp1 and NF-κB binding sites and presumed to be activated by Sp1 and NF-κB factors [20].…”
Section: Introductionmentioning
confidence: 99%